Application of resistance drilling to genetic studies of growth, wood basic density and bark thickness in Eucalyptus globulus. Issue 3 (2nd July 2020) - Nickolas, H.; Williams, D.; Downes, G.; Harrison, P. A.; Vaillancourt, R. E.; Potts, B. M.
ABSTRACT: Tree breeders are increasingly using resistance drilling (RESI) for the non-destructive assessment of wood basic density, but its application to the measurement of stem diameter at breast height (DBH) and bark thickness is less reported. Using Eucalyptus globulus progeny trials established with open-pollinated families from native trees representing 13 subraces, and adjusting bark thickness for its inherent phenotypic relationship with DBH, we: (1) quantified the genetic correlation between RESI and analogous traditional measurements of these traits; and (2) studied their genetic architecture and associations with subrace home-site climate. Significant variation was detected for all traditional and RESI-derived traits at the family and subrace level. High family and subrace-level correlations (>0.90) were found between RESI and traditional methods for all three traits. Bark thickness exhibited among the highest subrace differentiation ( QST > 0.63) reported to date for E. globulus, signalling divergent selection. Increasing bark thickness was positively associated with home-site temperature annual range and seasonality. Although subrace differentiation for wood density (RESI and traditional measures) was less ( QST  = 0.18–0.21), a similar climate association was detected, and the subrace-level correlation with bark thickness was positive and significant (0.61–0.75). However, the non-significant correlations between bark thickness and wood density at the family level suggest that selective covariance rather than pleiotropy have caused the correlated patterns of subrace variation. Variation in bark thickness (adjusted) and wood density was independent of DBH at the family and subrace level. Given the importance of these traits, RESI provides a useful approach for non-destructive assessments for silvicultural, genetics and ecological studies of forest trees.